Trace element contents in bottom sediments from the North Indian Ocean - Zinaida V Pushkina (PANGAEA, 1971)
Contents and distributions of Cu, Ni, Co, V, Cr, Zn, Pb, Mo, W, and Zr in near-coast and pelagic sediments of the Northern Indian Ocean are under consideration in the paper. Chemical analyses showed enrichment of pelagic clayey radiolarian oozes by Mn, Cu, Ni, Co, Pb, W, and Mo. According to enrichment factors these elements have the following order: Mo> Mn> Cu> Ni> Co> Pb> W. Enrichment of pelagic sediments from the Indian Ocean is mainly determined by the mechanism of the sedimentation process. Enrichment factors of Cu, Ni, Co, W, Mo, and Mn in pelagic sediments of the North Indian Ocean are intermediate between ones in pelagic sediments of the Pacific and Atlantic Oceans.
Supplement to: Pushkina, ZV (1971): Distribution of trace elements in sediments of the Indian Ocean to the south of Ceylon Island. Litologiya i Poleznyye Iskopaemyye (Lithology and Mineral Resources), 6(4), 34-45